A Last Interview with Lewis Aron: Recorded in June 2018, New York City. Issue 3 (2nd September 2022) - Ortúzar, Bárbara; Kuchuck, Steven
Abstract : In June, 2018, along with several of her colleagues from Chile, Barbara Ortuzar sat down for an interview with Lewis (Lew) Aron at the International Association for Relational Psychoanalysis and Psychotherapy (IARPP) conference in New York City. What follows is a transcribed account of that lively discussion. Following the interview, Steven Kuchuck was asked by Ortuzar and her colleagues to help with this project, particularly with regard to the translation, writing, and certain theoretical and biographical questions that arose in reviewing the recording and transcription. As it turned out, this would be the last conference that Lew would be able to attend, and as far as we know, the last interview he could grant. Lew's long battle with cancer came to an end just 8 months after the conversation that follows below.